Serum Endothelin-1 Correlates with Myocardial Injury and Independently Predicts Adverse Cardiac Events in Non-ST-Elevation Acute Myocardial Infarction - Anggoro Budi Hartopo; Indah Sukmasari; Ira Puspitawati; Budi Yuli Setianto (International Journal of Vascular Medicine)
Introduction. Serum endothelin-1 is increasingly released in acute myocardial infarction, by necrotic cardiomyocytes. In non-ST-elevation acute myocardial infarction (Non-STEMI), increased serum endothelin-1 on-admission may have clinical significance during acute hospitalisation events. Objective. The purpose of this study is to investigate whether increased serum endothelin-1 level predict adverse cardiac events in patients hospitalized with Non-STEMI. Methods. The design of this research was a prospective cohort study. Consecutive subjects with Non-STEMI undergoing symptom onset ≤24 hour were enrolled and observed during intensive hospitalization. Serum endothelin-1, troponin-I, and hs-C reactive protein were measured from peripheral blood taken on-admission. In-hospital adverse cardiac events were a composite of death, acute heart failure, cardiogenic shock, reinfarction, and resuscitated VT/VF. Results. We enrolled 66 subjects. The incidence of in-hospital adverse cardiac events is 13.6% (10 out of 66 subjects). Serum endothelin-1 level was significantly higher in subjects with in-hospital adverse cardiac events. Subjects with endothelin-1 level >2.59 pg/mL independently predicted adverse cardiac events in hospitalised Non-STEMI patients (adjusted odds ratio 44.43, 95% confidence interval: 1.44-1372.99, p value 0.03). The serum endothelin-1 level was correlated with serum troponin I level (correlation coefficient of 0.413, p value 0.012). Conclusion. Increased serum endothelin-1 on-admission correlated with increased troponin-I and independently predicted in-hospital adverse cardiac events in patients with Non-STEMI.